Boroquinol complexes with fused extended aromatic backbones: synthesis and optical properties - Elbert, Sven; Wagner, Philippe; Kanagasundaram, Thines; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2017)
Abstract Boron-based dyes are attractive synthetic targets due to their large variability of absorption and emission wavelengths. Through Pictet?Spengler cyclizations, followed by oxidation, π-extended boroquinols have been synthesized. During optimization of the reaction conditions, an unusual dearylation has been found and mechanistically investigated. For two of the synthesized boroquinols, mechanochromic effects with bathochromic shifts up to 50?nm were found upon grinding.